Prevalence of camel trypanosomosis and associated risk factors in Arero district, Borena Zone, Southern Ethiopia - Aden Giro; Kula Jilo (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
A cross-sectional study was conducted to determine the prevalence of camel trypanosomosis and assesses its associated risk factors in Arero district, Borena Zone, Oromia region, southern Ethiopia from November 2015 to March 2016. Blood samples were collected from randomly selected 385 camels. Giemsa-stained blood smears and Buffy coat technique were used for the detection of Trypanosomes infection. Out of 385 examined camels, 41 (10.65%) were positive for Trypanosoma evansi. There was statistically significant difference between age groups and trypanosome infection (P<0.05). Higher prevalence of the infection was recorded in Age group of >4 years (18.12%) followed by 3-4 years (6.98%) and <3 years old camels (4.67%) respectively. Higher infection was found in males (11.69%) as compared to female (10.39%) camels. However, there was no significant (P>0.05) difference in prevalence between sex and area of studies. The prevalence was varied among study localities within the district revealing the highest prevalence in Oroto (15.24%) and the lowest (5.66%) in Didole. A questionnaire survey was done to 50 camel owners to assess knowledge of the community about camel trypanosomosis. All respondents were familiar with the disease, its typical clinical signs and season of occurrence. The result of the current study revealed that camel trypanosmosis was relatively low prevalent in the study area. Thus, there is need of further study with the use of more sensitive diagnostic tests in order to establish effective control measures.